Performance and analysis of an ultraviolet C-band light emitting diode with an emission wavelength of 268 nm. (1st July 2022) - Zhang, Jianping; Zhou, Ling; Gao, Ying; Lunev, Alexander; Zhang, Bin; Götz, Werner
Abstract: We report a high-power ultraviolet C-band light-emitting diode (LED) with peak wavelength at 268 nm delivering 199 mW optical power at 350 mA direct current. The peak wall-plug and external quantum efficiencies are greater than 10% and 13%, respectively. We developed an approach to determine light-extraction efficiency (LEE) and internal quantum efficiency (IQE) based on the carrier recombination rate equation and used it to analyze the junction-temperature-dependent optical power behavior. For this LED, we obtained a LEE of ∼16% and a peak IQE of ∼83%. The efficiency droop percentage was quantified to be ∼20% at 350 mA, owing to Auger and other higher order carrier losses.